The global epidemiology of gastrointestinal cancers attributable to high-BMI: findings from the Global Burden of Disease Study 2021 - Yao, Laiang; Ji, Tao; Mu, Hailian; Xu, Xiangming (Frontiers in Nutrition, 2025)
BackgroundGastrointestinal (GI) cancers collectively account for over 30% of global cancer-related mortalities. Obesity is a well-established risk factor for GI cancers. We aim to investigate the temporal trends of GI cancer attributable to high BMI between 1990 to 2021 on global, regional and national levels.MethodsData was obtained from the Global Burden of Disease Study 2021. Deaths, Disability-adjusted life years (DALYs), and age-standardized rates (ASRs) were used to measure disease burden. Estimated annualized percent change (EAPC) were used to assess the temporal trend. We explored the association between SDI with high BMI-attributed GI cancer burden across 21 regions, 204 countries over the three decades.ResultsGlobally, between 1990 and 2021, all GI cancers had rising trends of deaths and DALYs attributable to high BMI. Colorectal cancer constituted the largest disease burden, with 99,268 (95% UI: 42,596–157,948) deaths and 1.17 (95% UI: 0.51–1.87) million DALYs in 2021. Liver cancer and pancreatic cancer had the sharpest increase in age-standardized rates, with EAPC exceeding 4 and 2%, respectively. Substantial heterogeneity was observed among the disease burden and temporal trends across regions. Higher SDI countries reported higher ASRs of GI cancers but showed declining trends with risk-attributable colorectal cancer, gallbladder and biliary tract cancer. Nearly all regions had increasing trends with the ASRs of high-BMI caused liver cancer and pancreatic cancer.ConclusionThe global burden of gastrointestinal cancers attributable to high BMI has increased substantially over the past three decades. We observed significant disparity with the temporal trends of different gastrointestinal cancers at various regions. Multi-level interventions, including lifestyle modification and tailored screening practice is required at global and regional levels to address the burden of gastrointestinal cancers attributable to high BMI.